Communication inequalities and health disparities among vulnerable groups during the COVID-19 pandemic - a scoping review of qualitative and quantitative evidence - Clara Häfliger; Nicola Diviani; Sara Rubinelli (BMC, 2023)
Abstract Background The COVID-19 pandemic has exacerbated health disparities in vulnerable groups (e.g., increased infection, hospitalization, and mortality rates in people with lower income, lower education, or ethnic minorities). Communication inequalities can act as mediating factors in this relationship. Understanding this link is vital to prevent communication inequalities and health disparities in public health crises. This study aims to map and summarize the current literature on communication inequalities linked with health disparities (CIHD) in vulnerable groups during the COVID-19 pandemic and to identify research gaps. Methods A scoping review of quantitative and qualitative evidence was conducted. The literature search followed the guidelines of PRISMA extension for scoping reviews and was performed on PubMed and PsycInfo. Findings were summarized using a conceptual framework based on the Structural Influence Model by Viswanath et al. Results The search yielded 92 studies, mainly assessing low education as a social determinant and knowledge as an indicator for communication inequalities. CIHD in vulnerable groups were identified in 45 studies. The association of low education with insufficient knowledge and inadequate preventive behavior was the most frequently observed. Other studies only found part of the link: communication inequalities (n = 25) or health disparities (n = 5). In 17 studies, neither inequalities nor disparities were found. Conclusions This review supports the findings of studies on past public health crises. Public health institutions should specifically target their communication to people with low education to reduce communication inequalities. More research about CIHD is needed on groups with migrant status, financial hardship, not speaking the language in the country of residence, sexual minorities, and living in deprived neighborhoods. Future research should also assess communication input factors to derive specific communication strategies for public health institutions to overcome CIHD in public health crises.